Pengenalan Identitas Kependudukan Digital di Dusun Cijolang, Desa Citengah, Kecamatan Sumedang Selatan: Facilitating Digital Population Identity Registration in Cijolang Hamlet, Citengah Village, South Sumedang District - Mahmud, Erlina Zulkifli; Sobarna, Cece; Afsari, Asri Soraya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This activity represents the implementation of an integrated Community Service Learning and Community Engagement program organized by the Faculty of Cultural Sciences, Universitas Padjadjaran, conducted in Cijolang Village to strengthen the community's capacity to utilize digital technology for public services. The program focused on facilitating the registration of Digital Population Identity through a door-to-door approach to expand service accessibility despite limited technological infrastructure and low levels of digital literacy. Assistance was provided through collaboration between village officials and the implementing team, offering technical guidance for the registration process and education on the use of digital applications for population administration and other public services. The program employed outreach and participatory methods that actively involved residents throughout its stages. The results indicate an improvement in the community's ability to operate digital technology and understand online administrative procedures. These findings demonstrate that the integrated program is effective in strengthening digital literacy within rural communities and can serve as a model for improving access to technology-based public services.